The Use of Digital Media to Improve Performance and Learning Skills in Bintan State Extraordinary Schools (SLB) - Deritawati Deritawati; Muhajir Muhajir; Nuril Huda (International Journal of Studies in International Education, 2025)
This study aims to explore the use of canva digital media in improving achievement and learning skills at the Bintan State Special School (SLB). In the digital era, inclusive education is a priority to provide equal opportunities for students with special needs. Digital media such as interactive learning apps, videos, and other digital aids are used to assist deaf, visually impaired, and students with other special needs in improving their learning abilities. This study uses a descriptive qualitative method, with participatory observation and interviews as data collection techniques. The results of the study show that the use of digital media at SLB Negeri Bintan contributes positively to increasing students' learning motivation and independence. The use of digital aids, such as voice-based applications and interactive videos, makes it easier for students to understand the subject matter, especially those with visual or hearing impairments. Despite challenges such as limited infrastructure and training for teachers, digital media has been shown to significantly improve student academic achievement. This study concludes that digital media has great potential to create a learning environment that is more inclusive, adaptive, and responsive to the needs of students with special needs. Appropriate technology support and increased training for educators will strengthen the implementation of digital media in learning at SLB.